2004
DOI: 10.1097/01.cmr.0000130006.46885.a0
|View full text |Cite
|
Sign up to set email alerts
|

The RAS-BRAF kinase pathway is not involved in uveal melanoma

Abstract: An activating mutation has been recently observed in cutaneous melanoma in a downstream component of RAS-BRAF. The most common mutation, occurring in 80% of cutaneous melanoma samples, is a T-to-A transition resulting in a single amino acid substitution (V599E). Since cutaneous and uveal melanoma (UM) have a common origin, we aimed to establish whether activation of the BRAF proto-oncogene is also an important factor in the development of UM. Exons 11 through 18 of the BRAF gene were screened from 33 primary U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Sequencing analysis confirmed that GNAQ is wild type in cell lines C918, Ocm1, Ocm3 and Mel285, while codon 209 of GNAQ is mutated from CAA (glutamine) to CTA (leucine) in cell lines Mel202 and 92.1 and to CCA (proline) in cell line Omm1.3. Cell lines Ocm1 and Ocm3 have BRAF V600E mutation (19, 20). AEB071 at low micromolar concentrations significantly decreased viability of all three GNAQ mutated cell lines (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequencing analysis confirmed that GNAQ is wild type in cell lines C918, Ocm1, Ocm3 and Mel285, while codon 209 of GNAQ is mutated from CAA (glutamine) to CTA (leucine) in cell lines Mel202 and 92.1 and to CCA (proline) in cell line Omm1.3. Cell lines Ocm1 and Ocm3 have BRAF V600E mutation (19, 20). AEB071 at low micromolar concentrations significantly decreased viability of all three GNAQ mutated cell lines (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Other pathways presumably regulate NF-κB activation in GNAQ wild type cells. For example, Ocm1 and Ocm3 cells have been shown to carry the common V600E BRAF mutation that constitutively activates the MAPK and NF-κB pathways (19, 20, 4446). High c-Met expression has been found in C918 and Mel285 cells (47) and it has been reported that NF-κB can be activated by HGF/c-Met signaling (48, 49).…”
Section: Discussionmentioning
confidence: 99%
“…However, enzastaurin did not significantly alter Erk1/2 phosphorylation in both cell lines, suggesting other PKC isoforms and/or PKC independent mechanisms for Erk1/2 activation in Ocm1 cells. Complicating this interpretation, Ocm1 cells have been shown to carry the common V600E BRAF mutation that constitutively activates the MAPK pathway [43], [44]. Furthermore, PKCα and PKCδ have been reported to activate Erk1/2 in mouse melanoma [51].…”
Section: Discussionmentioning
confidence: 95%
“…Ocular MM comprise about 3% of all MM and mucosal MM about 1% and patients with these subgroups have in general a worse OS than patients diagnosed with cutaneous MM [ 17 ]. In addition, mucosal MMs do only have a mutated BRAF gene in 6% of cases [ 18 ] while uveal MMs are not mutated [ 19 ]. Hence, the need for better treatments is especially pronounced for these two subgroups.…”
Section: Discussionmentioning
confidence: 99%